Finite Element Analysis of Concrete Beams Reinforced with Basalt Fiber-Reinforced Polymer - Sinthorn, Poramin; Kosittammakul, Anchalee; Tirapat, Supakorn; Foytong, Piyawat; Intarit, Pong-in; Sapsathiarn, Yasothorn; Kaewjuea, Wichairat; Thongchom, Chanachai; Chindaprasirt, Prinya (Salehan Institute of Higher Education, 2025)
The increasing demand for corrosion-resistant reinforcement in concrete structures has highlighted the potential of basalt fiber-reinforced polymer (BFRP) bars as a sustainable alternative to conventional steel reinforcement. However, the flexural behavior of BFRP-reinforced concrete beams remains insufficiently characterized, particularly through advanced numerical simulation. This study develops and validates a finite element model (FEM) to analyze the flexural performance of BFRP-reinforced concrete beams and to compare it with that of steel-reinforced beams. Eight beam specimens (200 × 300 × 3,100 mm), including six reinforced with BFRP bars and two with steel bars, were modeled under four-point bending using ANSYS software. The FEM predictions were validated against experimental data and benchmarked with the design provisions of ACI 440.1R-15 and CSA S806-12. The model showed strong agreement with experimental results, yielding ultimate load ratios of 0.92–0.94 for steel-reinforced beams and 1.01–1.45 for BFRP-reinforced beams. At higher reinforcement ratios, FEM predictions tended to overestimate the capacity of BFRP-reinforced beams. While steel-reinforced beams exhibited ductile failure, BFRP-reinforced beams failed in a brittle manner. The predicted moment-deflection responses and crack patterns closely matched both experimental observations and code-based predictions. This validated FEM provides a reliable computational framework for assessing and optimizing the design of BFRP-reinforced concrete beams, thereby advancing the application of non-metallic reinforcement in structural engineering. The findings also highlight challenges in accurately modeling concrete crushing and bond behavior within FEM, indicating directions for future refinement.